Duolingo application towards students’ English vocabulary mastery: A systematic literature review - Akhmad Renaldy; Elvina Arapah; Inayati Fitriyah Asrimawati; Emma Rosana Febriyanti (Information Technology and Science (ITScience), 2025)
Vocabulary plays a vital role in effective communication, academic success, and future opportunities, yet many students face difficulties in mastering a large number of words, understanding contextual usage, and pronouncing them correctly. With the rise of digital technology, language learning applications such as Duolingo have emerged as interactive and gamified tools that make vocabulary learning more engaging and accessible. This study aims to systematically review the studies on the effect or effectiveness of Duolingo in improving English vocabulary mastery among junior high school students through a systematic literature review. Using the PRISMA approach, twenty-four relevant experimental studies published between 2020 and 2025 were selected from databases such as Google Scholar and Semantic Scholar. The studies were analyzed descriptively to identify common patterns, methods, and outcomes related to the use of Duolingo in vocabulary instruction. The findings reveal that Duolingo consistently enhances students’ vocabulary achievement, motivation, and participation due to its game-based features and flexible learning environment. However, several studies highlight limitations such as the absence of comparative analyses with other learning tools and the limited exploration of long-term retention. Overall, the results confirm Duolingo’s potential as an effective supplementary tool for vocabulary learning, supporting educators in developing innovative and engaging English learning models. Further research is recommended to explore its integration into classroom settings and its impact on diverse learner groups.